Redesenhos políticos do corpo: uma análise de modos de circulação e concepção da dança on e off-line - Siedler, Elke (2016)
The use of the internet in various instances of life implies changes in cognitive processes, in order to generate changes in ways of doing, speaking and perceiving dance. The objective of this thesis is to reflect on the relational processes between body and dance, outlined in the interweaving of on-line and off-line environments. The main hypothesis is that there is production of knowledge in the on-off-line experiences flow, and this relationship can enhance the experience in dance activating the cognitive network that constitutes it. To understand these cognitive aspects, the research is grounded on the concept of "extended mind" (CLARK, 2003, 2008) and bodymedia theory (KATZ and GREINER, 2005). The on-off-line media convergence phenomenon (CASTELLs, 2009; JENKINS, 2009; SODRÉ, 2002) is analyzed as a metaphor (LAKOFF & JONHSON, 1999) for the organization and materialization of thoughts in dance. New ways of thinking-doing and enunciating dances are intrinsic to the processes of perceptual transformations (NOË, 2004). Thus, critical reflections are woven from examples that constitute the empirical corpus of the research such as artistic projects that show new ways to organize and materialize thoughts in dance and also projects responsible for dances displacement processes from the stage to the internet